STRUCTURAL IMPERFECTIONS OF ROSTOV REGION NATURAL MANAGEMENT: EFFECTS AND TERRITORIAL FEATURES - Ekaterina V. TOKSINA (Advanced Engineering Research, 2010)
Structural imperfections of the Rostov region natural management are considered. They underlie ecological problems and the effects on the natural and mental environment.